Digital editorial techniques in news websites: Exploring the use of podcasts and infographics - AL-Zoubi, Areen (International Journal of Innovative Research and Scientific Studies, 2025)
This study explores the editorial and presentation strategies for texts and information within digital media platforms, focusing on the use of podcasts and infographics on news websites. A descriptive-analytical approach was adopted, utilizing content analysis as the primary tool. The sample consisted of 15 podcasts and 15 infographics selected through random sampling from Al Arabiya and Sky News Arabia during the period from January 2 to January 21, 2025. The findings reveal that "current events" dominated the topics covered by both websites. The narrative style emerged as the most prevalent linguistic technique in podcasts, with Sky News Arabia excelling in storytelling, while Al Arabiya demonstrated stronger integration between audio elements and core messages. In terms of innovation, Al Arabiya focused more on guest hosting, whereas Sky News Arabia emphasized audience engagement techniques. Regarding infographics, Al Arabiya prioritized color clarity, while Sky News Arabia achieved better visual balance between text and images. The study concludes that digital platforms must diversify thematic coverage and further develop interactive strategies to enhance user engagement.